ДОКТРИНА «ЗНЯТТЯ КОРПОРАТИВНОЇ ВУАЛІ»: СУТНІСТЬ КОНЦЕПЦІЇ ТА ПЕРЕПОНИ ІМПЛЕМЕНТАЦІЇ В УКРАЇНІ - Makiyan, D.G. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2020)
The article is devoted to the research of the essence of the doctrine of "piercing of the corporate veil" and systematic legal analysis of the prospects of its implementation in the legal field of Ukraine. Numerous scientific works and visions of domestic scientists in this field have been analyzed and comparative analysis has been made. Traditionally, the fundamental legal value is the achievement of justice as a result of a dispute between the parties to certain legal relationships. For a long time, scholars and legal practitioners have been debating how and by what fundamental principle of law enforcement it is possible to secure a utopian state of justice-free society. At present, the result of such controversy is the development of two fundamental concepts that underpin the constitutions of most countries, the "rule of Law" and the "rule of legislation". The article also focuses on the potential conflict of constitutional legal norms with the analyzed doctrine in its current form and offers some options for modernization of modern Ukrainian legislation, taking into account the possibility of implementation of the corresponding concept. On the basis of the analysis of scientific works of other scientists in the field of law and their own research of the question, conclusions and proposals on the introduction of the doctrine of "piercing of the corporate veil" in the legal system of Ukraine were formulated. Today, there is good reason to argue that taking the first steps towards implementing the corporate veil doctrine by modernizing the provisions of current legislation will certainly contribute to Ukraine’s success in fulfilling its commitment to achieving the sustainable development goals that were pursued. officially approved by the UN General Assembly at the end of September 2015 and endorsed by our country. At the same time, the contradiction of the doctrine under study with other norms of law established at the level of the laws of Ukraine can be resolved by appealing to the Convention on Human Rights and Fundamental Freedoms and the ECtHR’s practice, which also serve as a source of law in Ukraine under the Law of Ukraine. "On the Enforcement of Judgments and the Practice of the European Court of Human Rights" of 23.02.2006 No. 3477-IV. On the other hand, it will not be superfluous to introduce certain changes aimed at modernizing the current economic legislation in the context of providing opportunities for applying the doctrine of "corporate veil" as proposed by other scholars. REFERENCES: 1. Karnaukh T.M. Doktryna "pidniattia korporatyvnoi vuali": sutnist ta perspektyvy zastosuvannia v Ukraini. Yurydychna Ukraina. 2013. No. 3. P. 53-60 [in Ukrainian].2. Dulska A. Piercing the corporate veil doctrine in international commercial arbitration: view from the Ukrainian perspective. Jurnalul Juridic National: Teorie si practica. 2016. APRILIE. P. 161-163.3. Zhornokui Yu.M. Doktryna "pronyknennia za korporatyvnu vual": svitovyi dosvid ta suchasni realii ukrainskoho pravozastosuvannia. Forum prava. 2016. No. 4. P. 127-132 [in Ukrainian].4. Shafeev K.A. Primenenie koncepcii snjatija korporativnoj vuali v mehanizmah zashhity prav cheloveka. Juvenis scientia. 2016. No. 4. P. 45-48. https://doi.org/10.15643/jscientia.2016.4.146 [in Russian].5. Agrotexim and other v. Greece, applications no 14807/89, judgment date 24/10/1995. Book Agrotexim and other v. Greece, applications no 14807/89, judgment date 24/10/1995. Strasbourg: European Court of Human Rights, 1995.6. Sabodash R.B. "Pronyknennia pid korporatyvnu vual" u praktytsi Yevropeiskoho sudu z prav liudyny. Korporatyvne pravo Ukrainy ta yevropeiskykh krain: pytannia teorii ta praktyky. Zb. nauk. pr. za materialamy XV Mizhnar. nauk.-prakt. konf. (6-7 zhovtnia 2017 r., m. Ivano-Frankivsk). Za red. V.V. Lutsia. Ivano-Frankivsk, 2017. P. 200-204 [in Ukrainian].7. Makhinchuk V.M. Obstavyny, yaki sud pryimaie do uvahy pry rozghliadi spravy pro zniattia korporatyvnoi vuali. Naukovyi visnyk Mizhnarodnoho humanitarnoho universytetu. Seriia: Yurysprudentsiia. 2015. Iss. 15(2). P. 40-42 [in Ukrainian].8. Makhinchuk V.M. Vyznachennia kontroliuiuchykh korporatsiiu osib kriz pryzmu doktryny zniattia korporatyvnoi vuali (piercing/lifting the corporate veil). Pryvatne pravo i pidpryiemnytstvo. 2016. Iss. 16. P. 55-60 [in Ukrainian].9. Makhinchuk V.M. Piercing the corporate veil (zniattia korporatyvnoi vuali): poniattia ta zmist doktryny. Naukovyi visnyk Khersonskoho derzhavnoho universytetu. Seriia: Yurydychni nauky. 2015. Iss. 3 (1). P. 136-140 [in Uk rainian].10. Makhinchuk V.M. Zarubizhnyi dosvid zastosuvannia doktryny zniattia korporatyvnoi vuali ta perspektyvy ostannoi v Ukraini. Sudova apeliatsiia. 2019. No. 1. P. 106-117 [in Ukrainian].11. Makhinchuk V.M. Do pytannia mozhlyvosti zastosuvannia doktryny "piercing the corporate veil" v pravi Ukrainy. Pravo i suspilstvo. 2015. No. 6 (3). P. 29-34 [in Ukrainian].12. Makhinchuk V.M. Zasady prytiahnennia do vidpovidalnosti kintsevoho benefitsiara (kontrolera) korporatsii cherez doktrynu pidniattia korporatyvnoi vuali: inozemnyi dosvid ta perspektyvy v Ukraini. Pryvatne pravo i pidpryiemnytstvo. 2019. Iss. 19. P. 42-49 [in Ukrainian].13. Vashulenko O.I. Perspektyvy implementatsii polozhen doktryny "zniattia korporatyvnoi vuali" do zakonodavstva Ukrainy v aspekti vidpovidalnosti materynskoi kompanii za borhamy dochirnoi. Porivnialno-analitychne pravo. 2017. Iss. 1. P. 45-49 [in Ukrainian].14. Blazhivska N.Ye. Piercing the Corporate Veil under ECtHR Jurisprudence. Eurasian Academic Research Journal. 2017. No. 12 (18). P. 21-27.15. Pereverzieva L.O. Pravovyi status dochirnikh pidpryiemstv: avtoref. dys. ... kand. yuryd. nauk: 12.00.04. NAN Ukrainy, In-t ekon.-prav. doslidzh. Kyiv, 2015. 19 p. [in Ukrainian].16. Postanova po spravi No. 910/7715/18 20.03.2019. Kasatsiinyi hospodarskyi sud. URL: http://reyestr.court.gov.ua/Review/80859527 [in Ukrainian].17. Ukhvala po spravi No. 757/21639/15-ts, provadzhennia No. 14-54tss19 07.02.2019. Velyka Palata Verkhovnoho Sudu. URL: http://reyestr.court.gov.ua/Review/80112288 [in Ukrainian].